New findings and complete recording for three turtles of conservation interest in the Bolivian Chaco - Cabrera, Mario R. (2024)
Fil: Cabrera, Mario R. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas, Físicas y Naturales. Instituto de Diversidad y Ecología Animal; Argentina.